Application of Fuzzy Logic in the Ranking of Academic Institutions. Issue 3 (3rd July 2019) - Das, Kousik; Samanta, Sovan; Naseem, Usman; Khalid Khan, Shah; De, Kajal
Abstract : For the development of any organization, evaluation of performance is an important task. To analyze the performance, Das et al. introduced a ranking framework based on fuzzy logic. That framework compared the current NIRF system of Indian Institutions with the fuzzy logic-based Mamdani system, KSM index. In that study, uniform membership functions are not taken. This study will focus on the ranking system based on Mamdani and Sugeno with fuzzy triangular numbers as input values of membership functions. Also, the updated results are compared with existing NIRF systems and considered Top 20 institutions of India for the year 2019 as per NIRF.